2020
DOI: 10.3390/ijerph17176345
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study of Posture and Fatigue of Neck According to Monitor Types (Moving and Fixed Monitor) by Using Flexion Relaxation Phenomenon (FRP) and Craniovertebral Angle (CVA)

Abstract: This study quantified the neck posture and fatigue using the flexion relaxation phenomenon (FRP) and craniovertebral angle (CVA); further, it compared the difference between the level of fatigue and neck posture induced by two types of monitors (regular fixed monitor and moving monitor). Twenty-three male participants were classified into two groups—the low-flexion relaxation ratio (FRR) group and the normal-FRR group, depending on the FRR value. All participants performed a document task for 50 min using both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…CV-angle analysis demonstrated that frequency of FHP was lower in the moving monitor than that in the fixed monitor. Hence, it could be concluded that sustained gazing at a fixed monitor can induce FHP [54]. In the present study, the author did not enquire about myopia among participants; and individuals who wore glasses were asked to remove them prior to CVangle measuring.…”
Section: Functional Improvement In Patients With Scs and Mmpmentioning
confidence: 85%
“…CV-angle analysis demonstrated that frequency of FHP was lower in the moving monitor than that in the fixed monitor. Hence, it could be concluded that sustained gazing at a fixed monitor can induce FHP [54]. In the present study, the author did not enquire about myopia among participants; and individuals who wore glasses were asked to remove them prior to CVangle measuring.…”
Section: Functional Improvement In Patients With Scs and Mmpmentioning
confidence: 85%
“…The processes of all participants were recorded on video so that the experimenter could review the results by assessing the video frames and double-checking the transfer time. In addition, the craniovertebral angle (CVA), an indicator used to measure the total forward curvature of the back, was estimated to analyze the participants’ postures ergonomically [ 44 , 45 ]. Before performing the RTT, the experimenter attached stickers to the three points, including the seventh cervical vertebra and tragus of the ear, to calculate the CVA.…”
Section: Methodsmentioning
confidence: 99%
“…[6] The craniovertebral (CV) angle can be measured as an objective way to evaluate head posture. [7] The "CV angle" is the angle created when a line extending from the tragus of the ear intersects a horizontal line going through C7. [7] This technique can accurately evaluate normal head-neck posture in the sagittal plane.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The "CV angle" is the angle created when a line extending from the tragus of the ear intersects a horizontal line going through C7. [7] This technique can accurately evaluate normal head-neck posture in the sagittal plane. There are several techniques for assessing posture, varying from manual methods like a goniometer, flexible ruler, and observational postural analysis by using the line of gravity to measurement through radiographic testing.…”
Section: Introductionmentioning
confidence: 99%